Cardiopulmonary resuscitation duration and favorable neurological outcome after out-of-hospital cardiac arrest: a nationwide multicenter observational study in Japan (the JAAM-OHCA registry) - Tasuku Matsuyama; Bon Ohta; Kosuke Kiyohara; Tetsuhisa Kitamura (Critical Care, 2022)
Abstract Objective We aimed to assess the association between cardiopulmonary resuscitation (CPR duration) and outcomes after OHCA. Methods This secondary analysis of a prospective, multicenter, observational study included adult non-traumatic OHCA patients aged ≥ 18 years between June 2014 and December 2017. CPR duration was defined as the time from professional CPR initiation to the time of return of spontaneous circulation or termination of resuscitation. The primary outcome was 1-month survival, with favorable neurological outcomes defined by cerebral performance category 1 or 2. We performed multivariable logistic regression analysis to investigate the association between CPR duration and favorable neurological outcomes. We also investigated the association between CPR duration and favorable neurological outcomes stratified by case features, including the first documented cardiac rhythm, witnessed status, and presence of bystander CPR. Results A total of 23,803 patients were included in this analysis. Multivariable logistic regression analysis demonstrated that the probability of favorable neurological outcomes decreased with CPR duration (i.e., 20.8% [226/1084] in the ≤ 20 min group versus 0.0% [0/708] in the 91–120 min group, P for trend < 0.001). Furthermore, the impact of CPR duration differed depending on the presence of case features; those with shockable, witnessed arrest, and bystander CPR were more likely to achieve favorable neurological outcomes after prolonged CPR duration > 30 min. Conclusion The probability of favorable neurological outcome rapidly decreased within a few minutes of CPR duration. But, the impact of CPR duration may be influenced by each patient’s clinical feature.